Garap Gendang Opok Kijing Ki Sarta Khas Karawang - Asep Wadi; Gelar Seftiyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is to reveal the function and position of the Sundanese opok kijing drum variety, which is claimed as one of the Sundanese drum varieties typical of Karawang Regency. This research method uses the Miles Huberman qualitative method and incorporates the theory of work from Rahayu Supanggah. The results of this study indicate that the opok kijing drum is indeed a Sundanese drum typical of Karawang Regency which is often used in Sundanese wayang golek art, or banjet masks as a complementary spice to the songs presented. The results of the creation of the opok kijing drum by Karawang artist Ki Sarta, are able to provide stimulus for Sundanese artists in West Java in terms of creativity, and can be applied to various types of traditional Sundanese musical accompaniment. The conclusion of the tepak gendang opok kijing/emprak kijing drum can be applied in various forms of contemporary art in today's era, such as Sundanese wayang golek, banjet masks, and Sundanese dangdut pop music that combines the pencug jaipong pattern. This tepak has an important function in the rhythmic structure because it is able to present a distinctive nuance that adds enthusiasm to the nayaga, juru kawih, and the audience. Keywords: Gendang Sunda, Opok Kijing, Ragam Tepak, Sarta.